PREVENTIVE ASPECTS OF BREAST MILK FEEDING IN PREMATURE INFANTS - I. A. Belyaeva; T. V. Turti; M. D. Mitish; E. P. Zimina; M. S. Rtishcheva; E. O. Tarzyan (Union of pediatricians of Russia, 2014)
This article is dedicated to the issue of infant feeding. It is universally recognized that the best product for neonatal and infant feeding is breast milk. On the basis of the worldwide literature data, the authors give a detailed account of breast milk advantages from various (biological, clinical and psychological) perspectives. They convincingly demonstrate that knowledge of preventive and medical aspects of breast feeding benefits allows conducting effective educational programs regarding motivation, struggle for breast feeding and long-term maintenance among medical personnel, mothers and their families. It is especially important to provide premature infants and sick children, who are often born unable to suck adequately, with breast feeding. The authors provide results of a study conducted at the SCCH demonstrating that special medical devices (nipples, feeding bottles) developed on the basis of studies of maternal breast sucking physiology facilitate a gradual transition from tube feeding to breast feeding.